Photocatalytic EDTA degradation on suspended and immobilized TiO2 - Mansilla, H. D. (2006)
The photocatalytic degradation of EDTA solutions (5 mM) has been studied under different conditions in the presence of TiO2 in suspensionor immobilized on glass rings and in the absence and presence of Fe(III). Using the response surface methodology, the initial pH, amount ofphotocatalyst, and the Fe/EDTA molar ratio were optimized in order to obtain better degradation. Under optimized conditions, 90% EDTAdegradation (at a 0.28 Fe/EDTA molar ratio) was reached after 60 min illumination at pH 3.0 and using 0.73 g L−1 TiO2. Increase of the acutetoxicity (Microtox) was observed in the course of the reaction, and degradation intermediates were identified by GC/MS analysis.